Becoming Turāth: the Islamic Tradition in the Modern Period - Elston, Mary (Die Welt des Islams, 2023)
In Egypt today, turāth (often translated as “heritage”, “legacy”, or “tradition”) is a pivotal concept for the Muslim religious scholars (ʿulamāʾ) of al-Azhar, the preeminent institution of Sunni learning located in Cairo. Although scholarly interest in turāth has grown in recent years, this literature has focused primarily on articulations of the concept at the hands of the Arab intelligentsia without attention to the ʿulamāʾ. To address this lacuna, and in so doing, offer a more complete understanding of the politics and contours of turāth debates in the contemporary Arab Muslim world, this article analyzes turāth in the writings and statements of ʿAlī Jumʿa (b. 1952), one of its most prolific interpreters amongst the contemporary Egyptian ʿulamāʾ. Sections one and two explore the semantic evolution of turāth in the intellectual genealogy within which Jumʿa locates his understanding of the concept, which includes two students of al-Azhar: Muḥammad ʿAbduh (1849–1905) and Ṭāhā Ḥusayn (1889–1973). The third section analyzes Jumʿa’s conceptualization of turāth and compares it to those of ʿAbduh and Ḥusayn. The article argues that Jumʿa’s representation of turāth is central to his efforts to reassert the intellectual and religious primacy of the ʿulamāʾ in the contemporary Muslim world.